Relevansi Pendekatan Semantik Pada Lirik Lagu “Bertaut” Karya Nadin Amizah Dengan Pembelajaran Teks Puisi - Elsa Novianti (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2024)
Literary works in the form of songs are a form of literary work that has lyrics or can be said to be poetry. When learning Indonesian, students do not understand the similarities between songs and poetry. This research aims to determine the semantic meaning of songs which are related to the physical structure of poetry and can be understood in learning Indonesian in poetry texts. The method used in the research is descriptive qualitative method. The techniques used in this research are note-taking and research techniques. The aim of this technique is to achieve a deep understanding of the meaning of the song "Bertaut" by studying the poetic text. The researcher conducted the research in stages, (1) understanding the content of the song lyrics, (2) including the song lyrics completely and completely, (3) analyzing some of the meanings of words related to the physical structure of the poem in the song lyrics, (3) explaining the results of the analysis, (4) summarizing the results of the analysis. The results of the research are that the structural similarities between the two are found in the meaning of the words and the language styles used such as hyperbole and connotation.